2007
DOI: 10.1080/09658210701276850
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete inhibition of emotion in specific autobiographical memories

Abstract: Emotional inhibition in recollection of specific autobiographical memories (Conway & Pleydell-Pearce, 2000) is investigated in two experiments. Less complete emotional inhibition was hypothesised to correspond to a reduced sense of psychological closure. Emotional inhibition was identified by comparing the effect of emotion words relative to lifetime period words as primes. In Experiment 1, emotion words facilitated recognition judgements of descriptions of remembered experiences rated low in closure. In Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 39 publications
(62 reference statements)
2
38
0
Order By: Relevance
“…Lardi et al (2010) found that integration is not related to affect changes, but making connections between the memory and one's personality is associated with a decrease in positive affect. Other studies (Beike, Adams, & Wirth-Beaumont, 2007;Beike & WirthBeaumont, 2005) have found that open memories (which may be non-integrative) elicit more intense emotions upon retrieval than closed memories (which may be integrative). Finally, individuals experience lower levels of distress while describing a traumatic or stressful memory if they express their subjective perspective or evaluation of it .…”
Section: Studymentioning
confidence: 95%
“…Lardi et al (2010) found that integration is not related to affect changes, but making connections between the memory and one's personality is associated with a decrease in positive affect. Other studies (Beike, Adams, & Wirth-Beaumont, 2007;Beike & WirthBeaumont, 2005) have found that open memories (which may be non-integrative) elicit more intense emotions upon retrieval than closed memories (which may be integrative). Finally, individuals experience lower levels of distress while describing a traumatic or stressful memory if they express their subjective perspective or evaluation of it .…”
Section: Studymentioning
confidence: 95%
“…Specific memories take longer to retrieve in response to affect cues than they do to activity and object cues (Robinson, 1976) or lifetime periods (Conway & Bekerian, 1987), and although Linton (1986) placed valence at the top of her hierarchy, she found emotion labels themselves to be very poor memory cues, as others have also found (Beike, Adams & Wirth-Beaumont, 2007;Reiser, Black & Abelson, 1985).…”
Section: Emotion and Autobiographical Memorymentioning
confidence: 92%
“…Measures included items about intensity of experienced regret and disappointment , personal responsibility, opportunity and motivation to remedy the life regret, a six-item measure of closure (Beike et al, 2007; a = .86 at immediate measure and .84 at follow-up), and two items assessing the intensity of emotion experienced at the time of the event and now. They also completed the PANAS (Positive and Negative Affect Schedule; Watson, Clark, & Tellegen, 1988; for positive affect, a = .86; for negative affect, a = .88) using a five point scale.…”
Section: Methodsmentioning
confidence: 99%
“…This sense of closure affects both the number of emotions the person recalls experiencing at the time, and the intensity of emotion the person experiences when recalling the event (Beike & Wirth-Beaumont, 2005). We employed a simpler way to manipulate closure, which also alters the emotional content of the memory: Participants were asked to consider ways in which their life regret was open (''unfinished business") versus closed (''a closed book") to them (Beike, Adams, & Wirth-Beaumont, 2007).…”
Section: Experimental Manipulations Of Mechanisms Of Interestmentioning
confidence: 99%
See 1 more Smart Citation